PRINCIPLES OF DEVELOPMENT OF FAMILISTIC COMPETENCE IN ADOLESCENTS (Scientific journal of the Fergana State University, 2024)
In this article, an opinion is given on the formation of familistic competence of adolescents, the manifestation of interest in the traditions and values of their own people and other peoples, the improvement of the lifestyle of adolescents, pedagogical and psychological characteristics.